EARTHQUAKE-RESISTANT HIGH RISE STEEL BUILDING STRUCTURE ANALYSIS WITH CHEVRON CONCENTRICALLY BRACE FRAME SYSTEM - Andina Prima Putri; Yudha Buana Putra; Christianto Credidi Septino Khala; Basyaruddin (Jurnal Infrastruktur, 2023)
In construction world, there’re several changes with times. The cause of changes is connected to building construction cases such as the structure failing to bear the load. Earthquake and tsunami load have potentials to make building structure become a failure. Indonesia experienced a lot of earthquake and tsunami, because Indonesia is located on three big plates encounters which Eurasia, Indo-Australia, and Pacific Plate. Banten province is one of province that has experienced earthquake and tsunami. In record of 10 years, Banten has experienced 3 earthquakes and 1 tsunami. Because of that, there must be a study on the design of steel structure buildings in Banten that resist earthquake and tsunami. Purpose of the research is to get structure value of building design. Design was done by numeric analysist method based on updated Indonesian National Standard about steel building planning. The result of study are, the biggest beam dimension is WF 300x200x9x12. The biggest column dimension is KC 700x300x13x24. Using adhesive plate with 14 cm thickness. Bracing dimension is WF 350x350x12x19. Beam connection with the most bolts has 3 M12 bolts and weld thickness 6 mm. Column connection between column with same dimension is planned with the most bolts has 16 M24 bolts. Column connection between two different column dimension is planned with the most bolts has 6 M24 bolts and weld thickness 8 mm. The biggest plate dimension is 90x90 cm. Brace connection is planned to have 6 M24 bolts and weld thickness 10 mm. Bottom structure stand with the biggest pile cap with seven 400 mm spun piles. Dimension of the biggest pile cap is planned to be 2700x2700x1000 mm with bar D25-300 on both x and y directions. The biggest pedestal column is planned to be 1100x1100x1000 mm with 24 D25 longitudinal bars and ϕ13-200 transverse bar. The Biggest tie beam is planned to be 400x600 mm in dimension with 4 D22 longitudinal bars and ϕ10-200.